TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP MADRASAH - Ahmad Juhaidi (Jurnal Pendidikan Islam, 2012)
This paper aims to assess alternative sources of education funding in madrasah through corporate social responsibility program (CSR). The approach used is descriptive analytic. The realization of CSR program is not perceived real yet by the madrasah. Previous research indicates that CSR tends to be more concerned with those who have power to influence the company (shareholders) and provides very little benefit to society and the environment. Madrasah, as one of the Islamic schools in Inodnesia, Has no strong bargaining power which results in receiving no fund allocation from CSR. Madrasah is potential to get this funding by considering the following aspects: 1) the location of madrasah gets direct impacts of the company, 2) the madrasah is participated in CSR program, 3) the madrasah has performed accountability/transparency security regarding financial management. In the company, CSR programs should ideally be used as a trade mark, as a form of corporate social responsibility to the public interest, particularly to the education in madrasah which commonly belongs to the public, but has minimum funding.